HUBUNGAN TIPE DASAR PERAIRAN DENGAN DISTRIBUSI IKAN DEMERSAL DI PERAIRAN PANGKAJENE SULAWESI SELATAN 2011 - Hidayanto Akbar; Sri Pujiyati; M. Natsir (Fakultas Perikanan dan Ilmu Kelautan, 2013)
The bottom on benthic substrate type of waters affect the distribution of demersal fish species. Type of the substrate in waters Pangkajene South Sulawesi dominated by muddy sand. The highest distribution of demersal fish was found in the depth of 10.45 m until 15.25 m with substrate muddy sand, demersal fish was the family of kakap or jenaha (Lutjanidae). Fish demersal in waters Pangkajene more influenced by the depth of waters than type of the substrate on the waters.